ANALISIS PENGARUH KEPUASAN KERJA DAN KETERLIBATAN KERJA TERHADAP KOMITMEN PROFESI DENGAN BUDAYA KOLEKTIVISME SEBAGAI VARIABEL MODERATING (Studi pada Perawat RSUD Kota Semarang) - Rizki, Shabrina Fella Fadhilah; Mas’ud, Fuad (Faculty of Economics and Business Diponegoro University, 2016)
This research aims to examine the effect of job satisfaction, job involvement that has been moderates by collectivism culture to the nurses in RSUD Kota Semarang. By using simple random sampling method, 87 persons are selected as the respondent. Analysis method which used in this research are validity and reliability test,classical assumptions test, and moderating regression analysis and hyphothesis testing.Analysis result demonstrates that job satisfaction and job involvement have positive and significant effect to professional commitment. Furthermore, collectivism culture moderates job satisfaction to professional commitment and moderates job involvement to professional commitment. The result of the analysis could be known that 67,1 percent variation of professional commitment could be explained by independent variable and moderating variable that has been examined, while 32,9 percent by the others variables outside this research.